(untitled) - Redmond, Tony (Amsterdam, 2005)
The new edition features key updates based on practical experience of working with Exchange 2003 since its release, including Service Pack 1 (SP1), plus detailed description of the new functionality included in Exchange 2003 and Outlook 2003
Keywords: Client/server computing,Máy tính khách/chủ